TANTANGAN PENERAPAN BLOCKCHAIN DALAM SISTEM E-VOTING DI INDONESIA - Dian Enjelia; Lamtiar Hema Malini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
As one of the coastal ecosystem-based green open spaces in North Jakarta, the Tol Sedyatmo Mangrove Ecotourism Area offers a nature-based tourism alternative that is highly relevant for urban communities. However, field observations reveal a notable gap between tourist expectations and the actual conditions of the area, particularly in terms of the availability and quality of supporting facilities as well as the sense of security felt throughout the visit. Against this backdrop, this study was conducted to examine the extent to which amenities and security influence tourist satisfaction in this area, both individually and simultaneously. This study was designed using a quantitative approach and carried out through a survey method. A questionnaire was used as the primary instrument to collect data from 100 tourists selected through purposive sampling. All collected data were subsequently processed and analyzed using multiple linear regression, preceded by validity and reliability testing as well as classical assumption tests encompassing normality, heteroscedasticity, and multicollinearity tests. Partial testing revealed that amenities have a positive and significant effect on tourist satisfaction, as does security, which was also proven to significantly influence tourist satisfaction. When analyzed simultaneously, the results further confirmed that amenities and security together significantly shape tourist satisfaction. The implications of these findings underscore the importance of managerial attention toward improving facility quality and strengthening the security system as the primary foundation for delivering a satisfying and sustainable tourism experience.